Development of neck dummy for head impact (soccer heading) experimental setup - Abdul Rahim, Zulkufli Ahmad (2013)
Heading a ball during soccer game will not affect to human health. But repeating similar action might cause serious injury especially onto human head. As head is one important part of human body, head need to be protected as well human body will have no further use if there is any damaged system at human brain. Due to this serious risk when perform repetitive ball heading, this study was conducted to assist head impact (soccer heading) experimental setup by developed a significant method in building neck dummy that can perform like real human neck. Using this dummy, accurate value of force impacted by the ball to the head can be measured. Besides, skull dummy that attached to the neck dummy will react as same way with real human head while heading the ball. So that is the purpose of neck dummy in this experimental setup. Besides using complete experimental setup including this neck dummy, risk of repeating ball heading by human can be measured using these dummies and human is unnecessarily needed to perform this kind of action.